Ethnomedicinal uses and in vitro anti-salmonella activity of indigenous herbal concoctions sold in the Bamenda food market for the treatment of typhoid fever - Tsouh Fokou, Patrick Valere; Junko Ntishi, Julliette; Ngo Teke, Gerald; Pinlap, Brice Rostan; Tchokouaha Yamthe, Lauve Rachel; Fekam Boyom, Fabrice (Ethnobotany Research and Applications, 2025)
Background: Typhoid fever remains a significant public health burden in Cameroon. Rising antibiotic resistance has made its treatment increasingly challenging. This study surveyed and assessed the anti-typhoid properties of herbal concoctions sold for typhoid fever treatment in the Bamenda Food Market Methods: Concoctions used to treat typhoid fever and their plant components were identified through an ethnomedicinal survey. Extracts were prepared via: infusion of dry powders, decoction of fresh plant parts, and direct drying of liquid concoctions. Anti-Salmonella activity was evaluated using the microdilution method against clinical isolates (S. typhimurium, S. enteritidis, S. paratyphi B, S. typhi) and a reference strain (S. typhimurium ATCC 14028). Results: The survey identified 18 typhoid-treatment concoctions sold in the Bamenda market (Mezam Division). These contained 33 plant species from 22 families, with leaves being the most common plant part used. Decoction and infusion were the primary preparation methods. In vitro testing revealed 5 concoctions with anti-Salmonella activity, exhibiting minimum inhibitory concentrations (MICs) between 2.5 and 10 mg/mL. Concoction P16 (Detarium senegalensis J.F.Gmel. and Cochlospermum tinctorium Perrier ex A.Rich.) showed the highest activity against multiple Salmonella strains (MIC range: 2.5–10 mg/mL). Conclusions: Concoction P16 demonstrated significant anti-typhoid activity in vitro. Further research is warranted to confirm these findings in animal models, identify its active compounds, and develop standardized formulations. Keywords: Ethnomedicinal survey; Typhoid fever; Antibiotic resistance; Herbal concoctions; Anti-Salmonella activity; Detarium senegalensis; Cochlospermum tinctorium; Bamenda food market